The War Titles of the Arabs Before Islam - قاسم جابر العلياوي, علي (Journal of College of Education, 2020)
This research is about (The War Titles of the Arabs Before Islam). These titles were given to some tribes or some people. These titles were derived from the war situations and its different phases, starting from forming alliances and preparing for fight, then the battle and its arms and what happens there like killing, wounding, resisting, fleeing, taking prisoners, seeking for revenge, holding reconciliation and paying blood money. The war titles were not given randomly. They had specific functions and meanings. They were used for praising or vilification, so they represented a social standard to enhance the positive sides of the fighters by the praising titles, and deterring the negative sides by the vilification titles